2007
DOI: 10.1007/s11099-007-0099-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topdressing on individual leaf photosynthesis at different position in direct-sown rice with non-woven fabric mulch system

Abstract: Direct sowing with non-woven fabric mulch is the new organic rice cultivation system. We studied the effect of topdressing on individual leaf photosynthesis at different position and grain yield in rice plants cultivated by this system. Leaf photosynthetic rate at the different leaf position per plant (P N-LP ) of the third and fourth to lower leaves was higher when the topdressing amount was increased. Without topdressing or in no-fertilizers plots, the P N-LP values of lower leaves were very low. The leaf ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…In rice, enhanced photosynthetic activity during the grain-filling period contributes most the final carbon content of the mature grain (Yoshida 1981, Peng et al 2004. Although a number of researchers have compared cultivar differences in photosynthetic capacity in rice, little attention has been paid to the N level and few have focused on the effects of supplemental N application on photosynthetic rate during the grain-filling stage (Hossain et al 2007). Recently, Hirasawa et al (2010) showed that different rates of supplemental N application shortly before heading result in differences in the photosynthetic rate among selected varieties of rice despite identical levels of leaf N. To determine how photosynthetic traits vary among different cultivars, it is necessary to compare the responses to leaf N changes among the cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…In rice, enhanced photosynthetic activity during the grain-filling period contributes most the final carbon content of the mature grain (Yoshida 1981, Peng et al 2004. Although a number of researchers have compared cultivar differences in photosynthetic capacity in rice, little attention has been paid to the N level and few have focused on the effects of supplemental N application on photosynthetic rate during the grain-filling stage (Hossain et al 2007). Recently, Hirasawa et al (2010) showed that different rates of supplemental N application shortly before heading result in differences in the photosynthetic rate among selected varieties of rice despite identical levels of leaf N. To determine how photosynthetic traits vary among different cultivars, it is necessary to compare the responses to leaf N changes among the cultivars.…”
Section: Introductionmentioning
confidence: 99%